2022
DOI: 10.1101/2022.11.06.515387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Upgrading Voxel-wise Encoding Model via Integrated Integration over Features and Brain Networks

Abstract: A central goal of cognitive neuroscience is to build computational models that predict and explain neural responses to sensory inputs in the cortex. Recent studies attempt to borrow the representation power of deep neural networks (DNN) to predict the brain response and suggest a correspondence between artificial and biological neural networks in their feature representations. However, each DNN instance is often specified for certain computer vision tasks which may not lead to optimal brain correspondence. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…These studies have shown that neural networks can effectively capture complex visual representations, and their performance improves with scale, as indicated by [3]. For problems involving predicting the brain's response to natural scenes, [5] demonstrated that voxel-wise encoding models, enhanced by integrating features from pre-trained neural networks and cortical network information, achieved the best performance. These techniques show promise in learning the brain's response to visual stimuli of natural scenes and understanding our brains.…”
Section: Introductionmentioning
confidence: 96%
“…These studies have shown that neural networks can effectively capture complex visual representations, and their performance improves with scale, as indicated by [3]. For problems involving predicting the brain's response to natural scenes, [5] demonstrated that voxel-wise encoding models, enhanced by integrating features from pre-trained neural networks and cortical network information, achieved the best performance. These techniques show promise in learning the brain's response to visual stimuli of natural scenes and understanding our brains.…”
Section: Introductionmentioning
confidence: 96%